Explosive Volcanism in a tuff-dominated Intraplate Setting, Sarmiento Formation (Middle Eocene- lower Miocene), Patagonia Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Sarmiento Formation (middle Eocene to early Miocene) represents the distal record of the activity of the Andean volcanic arc in central Patagonia, mainly dominated by accumulation and reworking of fine ash in a low-gradient continental setting. Intraplate volcanism takes place in the Golfo San Jorge Basin during the deposition of the Sarmiento Formation, and shallow intrusives and basaltic lava flows occurs. An exposure of basaltic volcaniclastic deposits was analyzed in the proximity of the Cerro Dragón intrusive rocks. These deposits consist of eight volcaniclastic lithofacies, organized in three distinct lithofacies association: volcaniclastic debris flow (lahar), base surge, and scoriaceous breccias of a strombolian-style eruption. Explosive volcanism is evidenced by the fallout of ballistic bombs over base surge and scoriaceous deposits, which produced bedding sags in the plastic lapilli. These deposits constitute the first published record of explosive volcanism (Strombolian) associated to the emplacement of the Oligocene alkaline volcanic rocks in the Golfo San Jorge Basin, generally considered as subintrusive or hypabissal intrusions.